How to measure, compare and evaluate electricity billing policies: towards an Indicator of tariff fairness and reasonableness - Hessling-Herrera, Franco-David (Sociedad y Economía, 2025)
Since basic energy services are increasingly considered with greater certainty as instruments of the right to energy, the tariff principle of fairness and reasonableness is an element that will allow measuring the degree of balance in each energy service regime. The challenge, then, is to generate an indicator that serves as a reference, and that is the main objective of this article. For this purpose, first, the presentation of a particular electricity regime, the Argentinean one, is addressed, and then the mechanics of operationalization of the concept of “fairness and reasonableness” to the Tariff Fairness and Reasonableness Indicator is discussed. Then, the mathematical formulation of the indicator is presented with a breakdown of how each variable is calculated, including the weighted factor. Finally, conclusions on this first attempt to measure the energy services tariff policy and projections on how to further refine the measurement instrument are presented.